Specification and time required for the application of a lime-based inside historic buildings - V. P. de FREITAS (2008)
Intervention in ancient buildings with historical and architectural value requires traditional techniques, such as the use of lime mortars for internal and external wall renderings. In order to ensure the desired performance, these rendering mortars must be rigorously specified and quality controls have to be performed during application. The choice of mortar composition should take account of factors such as compatibility with the substrate, mechanical requirements and water behaviour. The construction schedule, which used to be considered a second order variable, nowadays plays a decisive role in the selection of the rendering technique, given its effects upon costs. How should lime-based mortars be specified? How much time is required for the application and curing of a lime-based render? This paper reflects upon the feasibility of using traditional lime mortars in three-layer renders inside churches and monasteries under adverse hygrothermal conditions and when time is critical. A case study is presented in which internal lime mortar renderings were applied in a church in Northern Portugal, where the very high relative humidity meant that several months were necessary before the drying process was complete.